Renal Effects of Fetal Reprogramming With Pentaerythritol Tetranitrate in Spontaneously Hypertensive Rats - Man, Andy W. C.; Chen, Min; Wu, Zhixiong; Reifenberg, Gisela; Daiber, Andreas; Münzel, Thomas; Xia, Ning; Li, Huige (Frontiers in Pharmacology, 2020)
Aims: Current anti-hypertensive therapies cannot cure hypertension and a life-long medication is necessary. Maternal treatment may represent a promising strategy for hypertension treatment. We have previously shown that maternal treatment of spontaneously hypertensive rats (SHR) with pentaerythritol tetranitrate (PETN) leads to a persistent blood pressure reduction in the female offspring at age of 6-8 months. The underlying mechanisms include improved endothelial function resulting from long-lasting epigenetic changes. In the present study, we address the renal effects of maternal PETN treatment. Methods and Results: F0 parental SHR were fed with either normal chow or PETN-containing (1 g/kg) chow ad libitum from the time point of mating to the end of lactation period. The F1 offspring received normal chow without PETN from the time point of weaning (at the age of 3 weeks). At the age of 16 weeks, female PETN offspring showed lower blood pressure than the control. No difference was observed in male offspring. All following experiments were performed with kidneys from 16-weeks-old female offspring. Maternal PETN treatment reduced the mRNA and protein expression of angiotensin-converting enzyme (ACE) and basic fibroblast growth factor (FGF2), resulting from epigenetic modifications found at the proximal promoter regions. The expression levels of mineralocorticoid receptor (MR) and factors in the MR signalling pathway (Rac1 and Sgk1) were also reduced by PETN. Major profibrotic cytokines, including Wnt4, TNF-alpha, TGF-beta and MMP9, were down-regulated by PETN, which was associated with reduced collagen deposition and glomerulus sclerosis in the kidney of PETN offspring. In addition, PETN treatment also decreased the markers of inflammation and immune cell infiltration in the kidneys. Conclusions: PETN maternal treatment leads to epigenetic changes in the kidney of female SHR offspring. The reduced renal inflammation, alleviated kidney fibrosis and decreased MR signalling are likely to be mechanisms contributing to the observed blood pressure-lowering effect.